Efficacy and safety of secukinumab in patients with generalized pustular psoriasis: A 52‐week analysis from phase III open‐label multicenter Japanese study. Issue 9 (26th February 2016) - Imafuku, Shinichi; Honma, Masaru; Okubo, Yukari; Komine, Mayumi; Ohtsuki, Mamitaro; Morita, Akimichi; Seko, Noriko; Kawashima, Naoko; Ito, Saori; Shima, Tomohiro; Nakagawa, Hidemi
Abstract: Generalized pustular psoriasis (GPP) is a severe inflammatory skin disease characterized by the presence of sterile pustules covering almost the entire body and systemic symptoms such as fever. Secukinumab, a fully human‐recombinant anti‐interleukin‐17A monoclonal antibody was indicated for psoriasis vulgaris and psoriatic arthritis in Japan but is not yet investigated for GPP. In this phase III, open‐label multicenter single arm study, the efficacy and safety of secukinumab as monotherapy or with co‐medication was evaluated in 12 Japanese patients with GPP. All the patients received secukinumab 150 mg s.c. at baseline, week 1, 2, 3 and 4, and then every 4 weeks. Two non‐responders were up‐titrated to 300 mg. Change in GPP severity from baseline was evaluated by clinical global impression (CGI) categorized as "worsened", "no change", "minimally improved", "much improved" or "very much improved". Treatment success was achieved by 83.3% ( n = 10) of patients at week 16 (primary end‐point) with CGI evaluated as "very much improved" ( n = 9) and "much improved" ( n = 1). Moreover, the area of erythema with pustules improved as early as week 1 and resolved by week 16 in most of the patients. The improvements were sustained throughout 52 weeks. Over the 52‐week treatment period, secukinumab was well tolerated with no unexpected safety signals. Nasopharyngitis, urticaria, diabetes mellitus and arthralgia were the frequent adverse events reported. The data from this study shows that secukinumab can become one of the potent treatment options for GPP.